Character Formation through the Kulliyyatu-l-Mu’allimin al-Islamiyyah Curriculum - Ramadhan, Randa; Zakir, Supratman (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
Character education is a fundamental element of Islamic education that aims to shape morally grounded individuals through the integration of knowledge, Islamic values, and habitual practices. In the context of modern Islamic boarding schools, the curriculum of Kulliyyatu-l-Mu’allimin al-Islamiyyah plays a crucial role in students’ character development. Therefore, this study aims to analyze the impact of implementing the Kulliyyatu-l-Mu’allimin al-Islamiyyah curriculum on students’ character development in a modern Islamic boarding school that adopts this educational system. This study employs a descriptive qualitative method with a field research approach. Data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, curriculum administrators, educators, and students. Data analysis was conducted through data reduction, data organization, and conclusion drawing, with data validity ensured through source and method triangulation. The findings indicate that the implementation of the Kulliyyatu-l-Mu’allimin al-Islamiyyah curriculum is carried out in an integrated manner through formal instruction, boarding school activities, and residential life. This implementation has a positive impact on students’ character development, particularly in terms of discipline, responsibility, independence, sincerity, and leadership, which are grounded in the values of the Panca Jiwa. These findings affirm that the Kulliyyatu-l-Mu’allimin al-Islamiyyah curriculum represents an effective and relevant model of Islamic character education for application in modern Islamic boarding schools across diverse socio-cultural contexts.